PENGARUH PENAMBAHAN TEPUNG KEMANGI (Ocimum basilicum) SEBAGAI ADITIFPAKAN TERHADAP PENAMPILAN PRODUKSI ITIK PEDAGING - Christian Christian; Irfan Djunaidi; Muhammad Halim Natsir (Jurusan Produksi Ternak, Fakultas Peternakan, Universitas Brawijaya, 2016)
This research was intended to investigate effects of inclusion of flour basil leaves (Ocimum basilicum) as feed additives on production performances of hybrid duck. The material used for this experiment 100 Hybrid duck of 14 day of age. The method used in this research was field trial and arranged in Completely Randomized Design in 4 treatments and 5 replications with 5 Hybrid duck in each unit. The treatments were basal (P0), basal feed + 0,75% flour basil leaves (P1), basal feed + 1,25% flour basil leaves (P2), basal feed + 1,75% flour basil leaves (P3), and basal feed + 2,25% (P4). The variables measurd were feed intake, body weight gain, feed conversion ratio (FCR), and IOFC. Data were subjected to analysis of variance of the Completely Randomized Design, if there were significant influence would tested by Duncan’ s Multiple Range Test. The result showed that treatment did not significantly affected on feed intake, body weight gain, feed conversion ratio (FCR), but significantly affected (P<0,01) on IOFC. Basil leaf meal can not improving production performance and lowering IOFC value. Keyword: Flour Basil Leaves, feed additives, performances production, Hybrid duck